(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2018)
In evolutionary biology, the ability to cooperate may have determined the success of the human race over other races. In agriculture, it seems to be the key to increasing agricultural productivity to feed nine billion people. Thinking about it, the main scope of this work is to measure the cooperation - scientific collaboration - through the co-authorships analysis in the agriculture field of literature. The goal was to map the countries that collaborate scientifically in the food security area. We considered articles published in the last 20 years in Web of Science and the results were analyzed using the VOSviewer software. The results indicate that the gene (the term "gene") was the predominant theme in the density of the terms in the articles and also in the studied subjects. The United States is the country that most contributes, followed by China. These two countries also have the largest mutual collaboration, with 254 connections between them. Keywords: Cooperation. Co-author. Co-occurrence. Indicators. Agribusiness. Bibliometrics. Link: http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/6611/4666